Knowledge, attitudes and breast-feeding practices of postnatal mothers in Central India - Upadhye, Jayant V.; Mandlik, Milind R.; Upadhye, Aditi J.; Marathe, Sanjay M.; Matte, Abhay R.; Upadhye, Jayshree J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Breast feeding is vital for the health of baby & mother. It is of advantage to baby, mother, family, society and nation. Present study was carried out to evaluate knowledge, attitude and breast feeding practices of postnatal women. Methods: This cross-sectional study was carried out at immunization centre. 208 postnatal women were interviewed. Results: Out of 208 postnatal women, 148 women (71.15%) had delivery by caesarean section while 60 women (28.84%) had vaginal delivery. 118 women (56.73%) started breast feeding the baby within 2 hours of delivery, 52 women (25%) started breast feeding the baby after 24 hours of delivery, 26 women (12.5%) started breast feeding the baby after 2-6 hours of delivery while 12 women (5.76%) started breast feeding the baby after 6-24 hours of delivery. 174 women (83.65%) were giving exclusive breast feeding to their babies, 32 women (15.38%) were giving mixed feeding to their babies due to failure to thrive because of inadequate breast secretions. 28 (13.46%) preferred to give formula feeds while 7 (3.36%) preferred to give cow’s milk when needed. 180 (86.53%) intend or started weaning after 6 months while 28 women (13.46%) started weaning to their babies due to failure of baby to thrive or inadequate lactation. Conclusions: Awareness of breast feeding was good. Majority preferred exclusive breast feeding. Still, antenatal counseling about breast feeding can be further of advantage.